High-Throughput Zika Viral Titer Assay for Rapid Screening of Antiviral Drugs - Lee, Emily M. (Assay Drug Dev Technol, 2019)
Zika virus has recently emerged as a worldwide pathogen and public health burden due to its rapid spread and identification as a causative agent for multiple neurological defects, including congenital microcephaly. While there has been a flurry of recent research to address this emerging pathogen, there are currently no approved drug treatments for ZIKV infection. The gold standard for testing antiviral activity is to quantify infectious virion production. However, current infectious viral production assays, such as the plaque-forming or focus-forming unit assay, are tedious and labor intensive with a low-screening throughput. To facilitate drug development, we developed a Zika viral titration assay using an automated imaging system and an image analysis algorithm for viral colony quantification. This assay retained the principle of the classical virus titer assay, while improving workflow and offering higher screening throughput. In addition, this assay can be broadly adapted to quantification of other viruses.